Decolonial studies in the hegemonic circuits of Brazilian academic production - Carniel, Fagner (2024)
How are the Brazilian new research agendas influenced by the contemporary dissemination of theories challenging colonial ontologies and advocating for critical revitalization of Latin American thought? This article investigates the dominant circuits of academic knowledge production in Brazil to comprehend the impact of decolonial perspectives during the first decade of the reception and adoption of this theory in the country’s intellectual production. By examining 246 articles that explored the terms “decolonial” or “decolonials” published up to 2018, we aimed to analyze the various applications this category had within Brazilian research. The aim is to outline the structure of networks involved in decolonial studies through a bibliometric review of this literature, to provide a partial historical overview of the principal themes, authors, and references mobilized in periodicals registered in the Scopus and Web of Science between 2009 and 2018. The findings suggest that studies associated with decolonial perspectives presented as both analytical and political, organized within the field of social sciences but with a noticeable influence on other knowledge domains.